Comparison of Intravenous Tramadol and Morphine in attenuation of Hemodynamic Stress Response in Patients Undergoing Laparoscopic Cholecystectomy - Muhammad Shahid, Muhammad Usman Mohsin, Mudassar Ali, Talal Shahid, Muhammad Sarmad, Hafsa Tariq (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The primary objective of this study is to compare the efficacy of intravenous Tramadol and intravenous Morphine in attenuating the hemodynamic stress response during laryngoscopy and endotracheal intubation in patients undergoing laparoscopic cholecystectomy. Methodology: This Randomized controlled Trial study was conducted at Sahiwal Teaching Hospital, Sahiwal, from March 2023 to August 2023. In this research, 80 participants slated for laparoscopic cholecystectomy and aged between 20 and 50 years, with American Society of Anesthesiologists (ASA) Grade I or Grade II, were randomly assigned to two groups—Group-T (Tramadol) and Group-M (Morphine)—using a lottery method, each comprising 40 patients. Results: It was seen that SBP, DBP, MAP and heart rate Morphine group was lower than Tramadol Group. The mean recovery time of Tramadol and Morphine Groups was 46.29±8.65 minutes and 30.47±5.22 minutes, respectively. nausea & vomiting was noted as 14 (42.5%) and 6 (15.05), in Tramadol and Morphine Groups, respectively (p<0.001). It was seen that morphine was effective in 37 (92.5%) patients whereas tramadol was effective in 27 (67.5%) patients. Therefore, morphine was more effective than tramadol (p<0.001). Conclusion: Intravenous Morphine is more effective than intravenous Tramadol in attenuating the hemodynamic stress response to laryngoscopy and endotracheal intubation during laparoscopic cholecystectomy. Keywords: Cholecystectomy, Hemodynamic stress response, Intravenous morphine, Tracheal intubation, Tramadol.